Digital Lovers and Jealousy: Anticipated Emotional Responses to Emotionally and Physically Sophisticated Sexual Technologies - Ashton Prochazka; Robert C. Brooks (Human Behavior and Emerging Technologies)
Technologies that stimulate human social and sexual impulses could affect users and societies. Here, we report on two experiments designed to test participant responses to (1) “virtual friend” chatbots that vary in capacity to engage users socially and emotionally (i.e., emotional sophistication) and (2) “digital lover” technologies—in the form of sex toys, sex robots, or virtual reality entities—that vary in capacity to physically stimulate users (i.e., physical sophistication). Participants (173 female, 176 male) read vignettes that each described a particular technology and then answered whether, if their romantic partner were to use the described technology, they would anticipate jealousy or anger, and whether they would prefer to see the technology banned. Participant anticipations of jealousy and anger were so similar that we combined them in a single composite measure. In experiment 1, both the anticipation of jealousy-anger and the inclination to ban chatbots increased with emotional sophistication, particularly in female participants. In experiment 2, both sexes anticipated greater jealousy-anger and were more inclined to ban more physically sophisticated digital lovers. Female participants expressed higher levels of both responses across the range of sophistication. Experiment 2 participants were more likely to anticipate jealousy-anger and more inclined to ban sex robots than sex toys or virtual reality lovers. Our results show only limited consistency with evolutionary theories concerning sex differences in jealousy. Generally, the anticipated levels of jealousy-anger and inclination to ban the described technologies were low, suggesting low levels of resistance to the idea of the technologies.